Highly sensitive blood-based biomarkers detection of beta-amyloid and phosphorylated-tau181 for Alzheimer’s disease - Yang, Wei; Guan, Fulin; Yang, Lihui; Shou, Guangli; Zhu, Fangfang; Xu, Yuanyuan; Meng, Ying; Li, Min; Dong, Wanli (Frontiers in Neurology, 2024)
Background Plasma biomarker has the potential to be the reliable and propagable approach in the early stage diagnosis of Alzheimer’s disease (AD). However, conventional methods appear powerless in the detection of these biomarkers at low concentrations in plasma. Here, we determined plasma biomarker concentrations of patients across the AD spectrum by an improved digital enzyme-linked immunosorbent assay (ELISA) technique. Confirms the predictive and diagnostic value of this method for AD patients and study the relationships between these biomarkers and cognitive status. Methods Plasma concentrations of amyloid-beta 40 (Aβ40), amyloid-beta 42 (Aβ42) and plasma phosphorylated tau at threonine 181 (p-tau181) were determined in 43 AD patients, 33 mild cognitive impairment (MCI) patients and 40 normal cognition (NC) subjects as healthy controls using the improved digital ELISA technique. In addition, all subjects were required to receive neuropsychological assessments. Results Plasma p-tau181 level showed certain discrepancies between NC and MCI (p < 0.05), AD (p < 0.01) groups. The level of plasma Aβ42 (p < 0.05) and Aβ40 (p < 0.01) was significantly different between AD and NC group. The p-tau181 level was able to distinguish AD (AUC = 0.8768) and MCI (AUC = 0.7932) from NC with higher accuracy than Aβ42/Aβ40 ratio (AUC = 0.8343, AUC = 0.6569). Both p-tau181 (CDR: r = 0.388 p < 0.001; MMSE: r = −0.394 p < 0.001) and Aβ42/Aβ40 ratio (CDR: r = −0.413 p < 0.001; MMSE: r = 0.358 p < 0.001) showed stronger positive correlation with clinical dementia rating (CDR) and mini mental state examination (MMSE) scores than Aβ42 (CDR: r = −0.280 p = 0.003; MMSE: r = 0.266 p = 0.005) or Aβ40 (CDR: r = 0.373 p < 0.001; MMSE: r = −0.288 p = 0.002) alone. Conclusion Plasma p-tau181 level and Aβ42/Aβ40 ratio showed promising values in diagnosis of AD and MCI. Our results indicate that this improved digital ELISA diagnosis approach can facilitate early recognition and management of AD and pre-AD patients.